Dehydration of apple rings - Promnitz, Richard Henry George (Department of Chemical Engineering, 2023)
The effect of air humidity and velocity, tray surface and ring thickness, on the drying rates of apple rings, is reported. Drying rates for different apple slice thicknesses are correlated with the total moisture content of the fruit and the air relative humidity. Also reported are results on the simulation, both experimental and computational, for the parallel-flow industrial dehydrator drying process.